2017
DOI: 10.1158/1078-0432.ccr-16-0860
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Fibroblast Growth Factor Receptor 1 for Treatment of Soft-Tissue Sarcoma

Abstract: Altered FGFR1 signaling has emerged as a therapeutic target in epithelial malignancies. In contrast, the role of FGFR1 in soft-tissue sarcoma (STS) has not been established. Prompted by the detection and subsequent therapeutic inhibition of amplified FGFR1 in a patient with metastatic leiomyosarcoma, we investigated the oncogenic properties of FGFR1 and its potential as a drug target in patients with STS. The frequency of amplification and overexpression, as assessed by FISH, microarray-based comparative genom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 49 publications
(51 reference statements)
0
24
0
Order By: Relevance
“…This study revealed that FGFR inhibitor sensitivity in STS models is primarily determined by FGFR1 expression levels and supports further evaluation of FGFR inhibitor therapy in this group of diseases. 37 These first individual reports about successful personalized treatments and translational research projects originating from the MASTER program not only underscore the clinical need for broad testing of common genetic variants in rare and unclassifiable tumors, but also demonstrate the multitude of opportunities for translational research opened up by comprehensive genomic profiling in a clinical context.…”
Section: Beyond Case Reportsmentioning
confidence: 98%
“…This study revealed that FGFR inhibitor sensitivity in STS models is primarily determined by FGFR1 expression levels and supports further evaluation of FGFR inhibitor therapy in this group of diseases. 37 These first individual reports about successful personalized treatments and translational research projects originating from the MASTER program not only underscore the clinical need for broad testing of common genetic variants in rare and unclassifiable tumors, but also demonstrate the multitude of opportunities for translational research opened up by comprehensive genomic profiling in a clinical context.…”
Section: Beyond Case Reportsmentioning
confidence: 98%
“…The following antibodies were used: rabbit anti-FGFR1 (ab76464), rabbit antiClathrin heavy chain (ab21679), mouse anti-COTL1 (ab187608), and rabbit anti-SLC20A1 (ab177147) from Abcam; rabbit anti-FGFR1 (2144-1) from Epitomics; rabbit anti-VAMP4 (136002) from SYSY; mouse anti-phospho-FGFR (Tyr653/654) (#3476), rabbit anti-FGFR1 (#9740), rabbit anti-DYKDDDDK (FLAG) tag (#2368), rabbit anti-phospho-PLCG1 (Tyr783) (#14008), mouse anti-phospho-ERK1/2 (Thr202/Tyr204) (#9106), rabbit anti-RSK2 (#5528), rabbit anti-OAS1 (#14498) and rabbit anti-PTPN1 (#5311) from Cell Signaling Technology; mouse anti--tubulin (T6557), and mouse anti-FLAG M2 antibody (F-1804) from Sigma-Aldrich; mouse anti-EEA1 (610456) from BD transduction laboratories; rabbit anti-phospho-PLCG1 (Tyr783) (sc-12943-R), rabbit anti-FRS2 (sc-8318), and mouse anti-PLCG1 (sc-7290) from Santa Cruz Biotechnology; rabbit anti-HA epitope tag (600-401-384) from Rockland; mouse anti-MYC Tag (05-724) from Merck Millipore, human anti-EEA1 7 reading frame and XhoI and ApaI flanking sites into pEGFP-N1 cut with XhoI and ApaI using pcDNA3-hFGFR1 as template. pcDNA3-SBP-FGFR1 was made by introducing a sequence coding for the streptavidin-binding peptide (SBP) after the signal peptide in FGFR1 using a GeneArt Strings DNA fragment (Thermo Fisher Scientific).…”
Section: Antibodies and Compoundsmentioning
confidence: 99%
“…FGFR overexpression and activating 4 mutations have recently been demonstrated to play an important role in several types of cancer, including sarcoma (e.g. osteosarcoma, rhabdomyosarcoma (RMS) and soft tissue sarcoma) (4)(5)(6)(7)(8). In addition, the FGFR-specific downstream signaling adaptor, the FGFR substrate 2 (FRS2), is overexpressed in liposarcoma and renders these cells sensitive to FGFR inhibitors (9, 10).…”
Section: Introductionmentioning
confidence: 99%
“…RTKs are representative protooncogenes that are activated in various types of human cancers due to gene amplification, gene fusions, mutations in the coding region, or other alterations in the promoter/enhancer regions [8]. For example, FGFR family genes, including FGFR1, FGFR2, FGFR3, and FGFR4, are aberrantly activated in a variety of human cancers, such as breast cancer [9], cholangiocarcinoma [10], endometrial uterine cancer [11], gastric cancer [12], lung cancer [13], soft-tissue sarcoma [14], and urothelial carcinoma [15].…”
Section: Genomic Tests For Personalized Medicinementioning
confidence: 99%